2007
DOI: 10.1108/03074800710748803
|View full text |Cite
|
Sign up to set email alerts
|

Your place or mine? Face‐to‐face reference services across campus

Abstract: PurposeThe purpose of this paper is to present a case study which describes reference and instruction outreach programs promoted by the University of Texas at San Antonio (UTSA) Library. Direct‐2‐U Reference, Crash Courses, and Drop‐In Tours reached out to students in innovative ways to encourage non‐library users to see what they were missing and to give current library users even more choices. Direct‐2‐U Reference provided opportunities for students to get research help on their own turf. Librarians offered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…Using this approach, Mahaffy (2008) found an average of two students per week were assisted by a librarian co-located in the writing center three hours per week, however, there were some weeks with no referrals at all. Del Bosque & Chapman (2007) reported on a pilot which placed librarians in many locations across a campus, including the writing center. Over the course of 19 librarian-staffed hours at the writing center, only four reference interactions occurred.…”
Section: Alternative Service Pointsmentioning
confidence: 99%
“…Using this approach, Mahaffy (2008) found an average of two students per week were assisted by a librarian co-located in the writing center three hours per week, however, there were some weeks with no referrals at all. Del Bosque & Chapman (2007) reported on a pilot which placed librarians in many locations across a campus, including the writing center. Over the course of 19 librarian-staffed hours at the writing center, only four reference interactions occurred.…”
Section: Alternative Service Pointsmentioning
confidence: 99%
“…In essence it is anything occurring away from the confines of the reference desk" (1). Del Bosque and Chapman (2007) claim that a form of outreach gaining popularity is "taking reference to where the patrons are" (248). They name it "library-on-location", providing services to customers at the point of need and identify three common approaches that have been adopted: 1.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore all a roaming reference service needs to be a success is staff members who are willing to roam and any mobile device that can tell them where to go" (14). This is an interesting point as several studies have found library staff reaction to having to leave the relative security of the help desk can also be a hurdle that needs to be overcome if roving is to be a success (Del Bosque and Chapman 2007;Wagner 2004;Schmehl Hines 2007). Barrett, Acheson, and Luken (2010) in their introduction of roving at the University of Georgia, reported that it was perceived by library staff as being potentially intrusive to students and they were fearful that this proactive personalised form of help could appear aggressive.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on reference during nonbusiness hours are often part of a study or short-term trial, such as Direct-2-U reference in residence halls at the University of Texas at San Antonio (Del Bosque & Chapman, 2007), late night online service from 9:00 p.m. to 1:00 a.m. at Notre Dame University (Kayongo & Jacob, 2011), or the University of Buffalo's providing onsite reference and instruction in department spaces (Wagner & Tysick, 2007). These three studies provide insight to confirm that reference services are needed both in the evening and in other non-library spaces.…”
Section: Literature Reviewmentioning
confidence: 99%